Prevalence of pre-cluster symptoms in episodic cluster headache: Is it possible to predict an upcoming bout? - Pedersen, Adam Sebastian; Snoer, Agneta; Barloese, Mads; Petersen, Anja; Jensen, Rigmor Højland (Cephalalgia, 2021)
Background Early symptoms prior to a cluster headache bout have been reported to occur days or weeks before the actual beginning of the cluster headache bouts. This study aimed to describe the prevalence of pre-cluster (premonitory) symptoms and examine the predictability of an upcoming cluster headache bout. Methods 100 patients with episodic cluster headache were included in this retrospective cross-sectional study. All patients underwent a semi-structured interview including 25 questions concerning pre-cluster symptoms. Results Pre-cluster symptoms were reported by 86% of patients with a mean of 6.8 days (interquartile range 3–14) preceding the bout. An ability to predict an upcoming bout was reported by 57% with a mean 4.6 days (interquartile range 2–7) before the bout. Occurrence of shadow attacks was associated with increased predictability (odds ratio: 3.06, confidence interval: 1.19–7.88, p-value = 0.020). In remission periods, 58% of patients reported mild cluster headache symptoms and 53% reported occurrence of single shadow attacks. Conclusions The majority of episodic cluster headache patients experienced pre-cluster symptoms, and more than half could predict an upcoming bout, suggesting the significant potential of early intervention. Furthermore, the experience of mild cluster headache symptoms and infrequent shadow attacks in remission periods is common and suggest an underlying pathophysiology extending beyond the cluster headache bouts.